Guidelines of guidelines: focal therapy for prostate cancer, is it time for consensus?. (27th September 2022) - Ong, Sean; Chen, Kenneth; Grummet, Jeremy; Yaxley, John; Scheltema, Matthijs J.; Stricker, Phillip; Tay, Kae Jack; Lawrentschuk, Nathan
Abstract : Objective: To provide a summary and discussion of international guidelines, position statements and consensus statements in relation to focal therapy (FT) for prostate cancer (PCa). Methods: The European Association of Urology‐European Association of Nuclear Medicine‐European Society for Radiotherapy and Oncology‐European Society of Urogential Radiology‐International Society of Urological Pathology‐International Society of Geriatric Oncology and American Urological Association‐American Society for Radiation Oncology‐Society of Urologic Oncology guidelines were interrogated for recommendations for FT. PubMed and Ovid Medline were searched for consensus statements. Only studies in English since 2015 were included. Reference lists of the included articles were also interrogated and a manual search for studies was also performed. Results: Our results showed a lack of long‐term randomised data for FT. International Urological guidelines emphasised the need for more high‐quality clinical trials with robust oncological and toxicity outcomes. Consensus and positions statements were heterogenous. Conclusion: A globally accepted guideline for FT planning, technique and follow‐up are still yet to be determined. Well‐designed studies with long‐term follow‐up and robust clinical and toxicity endpoints are needed to improve our understanding of FT and create uniform guidelines to streamline management and follow‐up.